Efek Temperatur dan Waktu Terhadap Total Kandungan Antioksida Dari 5 Jenis Tanaman Herbal dengan Metode Phenanthroline Termodifikasi - Arman, Etriyanto; Yefrida, Y.; Refinel, R. (Departemen Kimia Universitas Andalas, 2023)
This research determines the effect of temperature, maceration time, extract storage time at room temperature and refrigerator temperature of the total antioxidant content in miana leaves (Plectranthus scutellarioides (L.)R. Br), papaya leaves (Carica papaya), rambutan leaves (Nephelium lappaceum), bay leaves (Eugenia polyantha) and green betel leaves (Piper betel L). The determination of total antioxidant content was carried out by modified phenanthroline method. Based on the research data. It was found that the optimum conditions for total antioxidant content in the samples above were at 100oC with 60 minutes of maceration time and without storage time of the extracted samples before being analyzed. The total antioxidant content of miana leaves, papaya leaves, rambutan leaves, bay leaves, and green betel leaves analyzed in the optimum conditions are 3.0865; 1.1554; 0.4641; 0.6764; and 3.3630 mmol Fe/g DW, respectively.